Performance and emissions study of a single cylinder ci engine using castor oil biodiesel - Jamaludin, Mohd Zaini (UTeM, 2018)
Since the scarcity of fossil fuel, an increase in oil prices and food crisis in the past, several techniques have been proposed for the production of this fuel which is totally or partially derived from renewable feedstock. This interest led to expose a renewable fuel that would supplement the current reserves, either directly or indirectly. Biodiesel is a substitute to conventional diesel fuel made from renewable resources, such as non-edible vegetable oils. The purpose of this study was to investigate the effects of biodiesel fuel derived from Castor oil blended with petro-diesel fuel at various blending ratios on performance and emissions. This study used a small four strokes diesel engine that operates through varied engine speeds at 1500, 2000, 2500, 3000, 3500 and 3600 rpm under 0, 50 and 100% dynamometer loads condition with an emission gas analyser attached to the exhaust pipeline. Data for this study were collected from experimental in term of power, torque, fuel consumption and gases emissions. Four samples were selected from Castor oil biodiesel which are B5, B10, B20, and B25 and diesel. On the basis of the results of this research, it can be concluded that the Castor oil biodiesel has a potential to be used as an alternative to replace biodiesel made from food (edible) source.